PROVISION OF REHABILITATION OF DRUG ADDICTED CHILDREN AS A FORM OF FULFILLMENT OF CONSTITUTIONAL RIGHTS - Eleanora, Fransiska Novita (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2020)
The aim of this research is to find out rehabilitation both in the form of medical and social assistance given to minors as addicts to narcotics, which can endanger lives and bodies, so that by carrying out rehabilitation gradually the child can return to the original condition with the recovery he has obtained. Besides giving in rehabilitation is a form of recognition and appreciation for the constitutional rights of citizens, where these rights are constitutional rights that have been contained in the 1945 constitution and those rights are rights protected by the government, and the state is also law, rights that are constitutional here in relation to is the right to health and the right to adequate housing, and the existence of integrated recovery both physically, mentally and socially so that children as addicts of narcotics can be accepted again in society, bearing in mind that children are the buds of the nation which will carry forward the ideals and struggle of the nation, so that it must be restored to the condition of the psyche and his health, because by restoring his condition will return to carry out activities or activities in gaining knowledge by learning, getting education and playing with his friends as usual, it can be said that the child as an addict from narcotics has returned to his normal environment and made a process of interaction in general . The formulation of the problem to be examined is whether the provision of rehabilitation of children as addicts of narcotics is part of the realization and recognition of constitutional rights in accordance with the constitution of the constitution by 1945. The method in this study uses juridical and normative that is using literature related to the problem to be investigated and can answer existing problems, where the results are that medical and social rehabilitation given to children as addicts of narcotics can provide recovery and return it to the psychological condition in a psychological way. integrated through physical, psychological and social health, and this is also a guarantee and protection from the government in fulfilling its constitutional rights as citizens, because by fulfilling the guarantee and recognition including the protection of children's rights, protection of the rights the most essential is the protection of the rights in his life to obtain opportunities in education and also health and play.keywords ; rehabilitation, children, narcotics, constitutional rights